Ground-up Java - Heller, Philip (Sybex, 2004)
This one-of-a-kind book teaches beginning programmers how to use the fastest-growing programming language, Java. In addition to learning the core Java language, you will also acquire a broad understanding of vital programming concepts, including variables, control, memory, indirection, compilation, and calling. Best-selling Java book author and popular Java University educator Philip Heller understands what you need to learn and knows how best to convey it. The companion CD includes animated, interactive games for each chapter that illustrate key concepts and give you deeper insights into the workings of Java.